ULTRASOUND ELASTOGRAPHY OF THE LIVER, SPLEEN, AND KIDNEYS IN CLINICALLY NORMAL CATS. Issue 4 (20th December 2013) - White, Jennifer; Gay, John; Farnsworth, Raelynn; Mickas, Matt; Kim, KwangGi; Mattoon, John
<x xml:space="preserve">Abstract</x> A large amount of overlap exists in the B‐mode ultrasound appearance of normal and abnormal liver, spleen, and kidney tissues in cats. Therefore, invasive tissue sampling procedures remain the standard method for diagnosing diseases in these organs. The purpose of our study was to assess the feasibility of ultrasound elastography as a technique for improving noninvasive characterization of the feline liver, spleen, and kidneys. Elastography was performed on 10 unsedated, clinically healthy cats. Numeric (strain) values (0 = softest to 255 = firmest) assigned to color pixels within regions of interest resulted in median scores (interquartile ranges) of body wall, 207.50 (189.75–224.00); liver, 119.00 (105.00–138.25); spleen, 127.50 (121–00–142.00); right renal cortex, 83.50 (64.00–130.00); right renal near field, 125.50 (110.75–139.75); left renal cortex, 77.50 (52.00–116.25); and left renal near field, 126.00 (114.00–145.25). Strain values were not different between organs. Body wall median was the only significantly different value (P < 0.05). Strain ratio values of body wall:organ were as follows: liver, 1.76 (1.38–2.00); spleen, 1.68 (1.47–1.83); right renal cortex, 2.31 (1.61–3.15); right renal near field, 1.62 (1.41–2.01); left renal cortex, 2.66 (1.45–4.13); and left renal near field, 1.51 (1.29–1.89). Subjectively, hepatic and splenic parenchymal tissues were homogeneous in compressibility and similar in elasticity to one another. Renal cortical tissue was softer compared to medullary tissue. Findings indicated that ultrasound elastography is a feasible technique for objectively and subjectively characterizing the feline liver, spleen, and kidneys. Further research is needed in cats with confirmed diseases of these organs, to compare the diagnostic sensitivity of ultrasound elastography vs. B‐mode ultrasonography.